Konsep Bela Negara dalam Perspektif Islam dan Kristen Protestan - Sir, Tomi Azis Khan; Wanto, Sugeng; Siregar, Husna Sari (ANWARUL, 2023)
The background of this research is that the authors are interested in conducting further research related to the Concept of State Defense in an Islamic and Christian Perspective because they want to know more about the concepts of the Koran and the Bible regarding state defense and how Islam and Christianity respond to state defense. Therefore, the author conducted a study entitled: "The Concept of State Defense in the Perspective of Islam and Protestant Christianity". The type of research that the authors conducted was library research, namely survey techniques used to collect data and information from various types of materials such as books, newspapers, magazines, journals, theses related to the discussion of this research, and several other works related to researcher this Tian. While the presentation of the data is qualitative. The results of the research findings that have been carried out can be stated as follows: State defense in an Islamic perspective is in Islam, jihad aims to defend, maintain, and also elevate the religion of Allah (Islam). Islam permits jihad or defending the country as long as it is not with war. Where to reject tyranny, to respect places of worship, to guarantee the independence of the homeland, eliminate slander, and guarantee the freedom of everyone to embrace their respective religions. Protestant Christianity explains that the participation of Protestant Christians in defending the country in life, nation and state should always try to make a contribution to the state. Defending the country is synonymous with the values contained as a mandatory action for every citizen. For Islam peace and if the country is good depends on the actions of their people, and always as a guide is the Al-Qur'an and Hadith to make the country better. The Qur'an also explains obeying Allah SWT, Rasulullah and ulil amri according to Allah's teachings. Meanwhile, in the Protestant Christian concept of defending the country that they think that the country is God, the formation of the country is from God, if they submit to the state then submit to God.